Strategies for Leadership in Management College Libraries - Vijayakuamar, M.; Manoj Kumar, K. S. (Journal of Information and Knowledge, 2016)
This paper is based on a MPhil thesis submitted to the Alagappa University. Survey method is used to collect the primary data for the study using a questionnaire administered to a random sample of management college library staff to identify the strategies employed for leadership among management libraries in Karnataka. The results suggest that librarians use a combination of various personal and professional strategies.